2021
DOI: 10.3390/ijms23010463
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Thermostability of a Fungal GH11 Xylanase via Fusion of a Submodule (C2) from Hyperthermophilic CBM9_1-2

Abstract: Xylanases have been applied in many industrial fields. To improve the activity and thermostability of the xylanase CDBFV from Neocallimastix patriciarum (GenBank accession no. KP691331), submodule C2 from hyperthermophilic CBM9_1-2 was inserted into the N- and/or C-terminal regions of the CDBFV protein (producing C2-CDBFV, CDBFV-C2, and C2-CDBFV-C2) by genetic engineering. CDBFV and the hybrid proteins were successfully expressed in Escherichia coli BL21 (DE3). Enzymatic property analysis indicates that the C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Table 2 showed that the EcsXyl4 has 227 hydrogen bonds, while CFxyl3 and EcsXyl1-3 only have 224, 216, 220, and 226, respectively, which results in a more thermal stability for EcsXyl4 than for other xylanases. In a previous study, the thermal stability of a xylanase from N. patriciarum increased after insertion of a CBM9_1-2, which attributed to four additional hydrogen bonds (S42–S462, T59–E277, S41–K463, and S44–G371) ( Miao et al, 2022 ). Figure 2E shows the 3D structure of EcsXyl4.…”
Section: Resultsmentioning
confidence: 95%
“…Table 2 showed that the EcsXyl4 has 227 hydrogen bonds, while CFxyl3 and EcsXyl1-3 only have 224, 216, 220, and 226, respectively, which results in a more thermal stability for EcsXyl4 than for other xylanases. In a previous study, the thermal stability of a xylanase from N. patriciarum increased after insertion of a CBM9_1-2, which attributed to four additional hydrogen bonds (S42–S462, T59–E277, S41–K463, and S44–G371) ( Miao et al, 2022 ). Figure 2E shows the 3D structure of EcsXyl4.…”
Section: Resultsmentioning
confidence: 95%
“…The C2 submodule had a considerable influence on improving the CDBFV's thermostability, according to enzymatic property study. The half-lives of the three chimaeras C2-CDBFV, CDBFV-C2, and C2-CDBFV-C2 are 1.5 times (37.5 min), 4.9 times (122.2 min), and 3.8 times (93.1 min) higher than wild-type CDBFV (24.8 min) at the ideal temperature (60.0°C) [55].…”
Section: Genetic Engineeringmentioning
confidence: 90%
“…For example, the catalytic efficiency of the Paenibacillus xylanase, using birchwood xylan as substrate, was increased by 1.5 fold after the introduction of a xylan-binding domain [ 34 ]. Furthermore, inserting the submodule C2 from Carbohydrate-binding modules 9_1-2 into the N- and/or C-terminal regions of Neocallimastix patriciarum xylanase increased (18–28%) its catalytic activity toward corncob xylanase [ 35 ]. In the present study, the proline-rich C-terminal oligopeptide enhanced the catalytic activity of xylanase by 2.48 fold, which is a remarkable effect in this type of studies.…”
Section: Discussionmentioning
confidence: 99%